2023
DOI: 10.1002/advs.202204488
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Temperature Synthetic Route Toward a High‐Entropy 2D Hexernary Transition Metal Dichalcogenide for Hydrogen Evolution Electrocatalysis

Abstract: High‐entropy (HE) metal chalcogenides are a class of materials that have great potential in applications such as thermoelectrics and electrocatalysis. Layered 2D transition‐metal dichalcogenides (TMDCs) are a sub‐class of high entropy metal chalcogenides that have received little attention to date as their preparation currently involves complicated, energy‐intensive, or hazardous synthetic steps. To address this, a low‐temperature (500 °C) and rapid (1 h) single source precursor approach is successfully adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…For example, the 2D HE metal disulfide (CrMnMoWRe)­S 2 shows significantly enhanced electrocatalytic hydrogen evolution performance compared to the parent MoS 2 (Figure b) . A combination of experimental and computational analysis showed that while the electrochemically active surface area increased by around 2×, the catalytic activity increased by 8×.…”
Section: Advantages Of High-entropy Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the 2D HE metal disulfide (CrMnMoWRe)­S 2 shows significantly enhanced electrocatalytic hydrogen evolution performance compared to the parent MoS 2 (Figure b) . A combination of experimental and computational analysis showed that while the electrochemically active surface area increased by around 2×, the catalytic activity increased by 8×.…”
Section: Advantages Of High-entropy Materialsmentioning
confidence: 99%
“…54 The DFT calculations further showed that combinations of elements improved the E ads , even when only two elemental substitutions of Mo for Mn and Cr at the MoS 2 surface were considered, demonstrating the synergistic effect of multiple elements within a local area. 34 ■ TRADITIONAL SOLID-STATE SYNTHETIC ROUTES TO HE MATERIALS Myriad approaches have been used for the synthesis of HE alloys, oxides, and chalcogenides, and have already been reviewed elsewhere in more detail than will be covered here. 8,55−57 The seminal work on HE materials by Cantor and Yeh both employed electrical heating of the constituent elements.…”
Section: ■ Advantages Of High-entropy Materialsmentioning
confidence: 99%
See 3 more Smart Citations